Transcriptome and metabolome analysis of Atractylodes lancea across different developmental stages - Zhang, Guanyu; Zhao, Zhiqiang; Li, Yaqian; Zhang, Leheng; Lu, Jimei; Qi, Kangru; Liang, Hua; Zha, Liangping; Xie, Jin (Frontiers in Plant Science, 2025)
Atractylodes lancea (Thunb.) DC is a medicinal plant known for its rhizome's production of valuable sesquiterpenoids, although the molecular mechanisms underlying their biosynthesis are not well understood. This study utilized integrated metabolomic and transcriptomic analyses to examine terpenoid dynamics across four developmental stages (June, July, September, November) in A. lancea. Metabolite profiling indicated distinct accumulation patterns: monoterpenoids reached their peak in July, while sesquiterpenoids were most abundant in September. Transcriptome analysis revealed the presence of 36 structural genes linked to the mevalonate (MVA) and methylerythritol phosphate (MEP) pathways, alongside 55 terpene synthase (TPS) genes. Subsequent phylogenetic analysis categorized the TPS genes into distinct subfamilies, and within the TPS-a subfamily, a comprehensive screening process considering significant correlations with terpenoid metabolites and the preservation of key conserved motifs identified eight candidate genes, including AlTPS21 and AlTPS42. Functional characterization demonstrated that the AlTPS21 protein catalyzes the conversion of farnesyl diphosphate to δ-cadinene and α-cadinol, while the AlTPS42 protein catalyzes the conversion of farnesyl diphosphate to δ-cadinene and α-copaene. Subcellular localization studies showed that both enzymes are localized to the nucleus and cell membrane. These findings enhance the understanding of the temporal regulation of terpenoid biosynthesis in A. lancea and provide crucial genetic insights for future metabolic engineering efforts.